2009
DOI: 10.1021/ja903369q
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Complex of an [OSSO]-Type Diphenolate Ligand Bearing trans-1,2-Cyclooctanediylbis(thio) Core: Synthesis, Structure, and Isospecific 1-Hexene Polymerization

Abstract: Six-coordinated dibenzyl Zr complex bearing an [OSSO]-type tetradentate ligand was synthesized, and the structure was fully characterized by NMR spectroscopy and X-ray crystallography. The zirconium complex has C(2) symmetry in solution. Owing to an effect of the cyclooctane ring structure, the combination of the zirconium complex and B(C(6)F(5))(3) or (Ph(3)C)[B(C(6)F(5))(4)] as the activator exhibited high activity toward polymerization of 1-hexene to yield highly isotactic poly(1-hexene).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 20 publications
5
62
0
Order By: Relevance
“…Recently, Ishii and co-workers have reported a zirconium complex of a tetradentate [OSSO]-type diphenolate ligand that bears a trans-1,2-cyclooctane diylbisA C H T U N G T R E N N U N G (thio)core and was effective in isospecific 1-hexene polymerization. [4] In material science or chemical research, the rational design of new o-carborane-derived materials has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ishii and co-workers have reported a zirconium complex of a tetradentate [OSSO]-type diphenolate ligand that bears a trans-1,2-cyclooctane diylbisA C H T U N G T R E N N U N G (thio)core and was effective in isospecific 1-hexene polymerization. [4] In material science or chemical research, the rational design of new o-carborane-derived materials has attracted much attention.…”
Section: Introductionmentioning
confidence: 99%
“…ZrCl 4 and HfCl 4 were treated with 1 a to give six-coordinated zirconium complex [Zr(OC 6 H 2 tBu 2 -4,6) 2 -…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, catalysts based on phenoxy-imine complexes may be not only more active than the metallocene catalysts, but they make it possible to produce a variety of polyolefinic materials, inclusive of ultra-high-molecular-weight PEs, welldefined multimodal PEs, selective vinyl-and Al-terminated PEs, isotactic and syndiotactic PPs, as well as stereo-and regioirregular high-molecular weight poly(1-olefin)s [1]. Group 4 transition metal complexes which incorporate tetradentate [OSSO]-type bis(phenolate) ligands have also been quite extensively studied in homo-and copolymerization of olefins as well as in polymerization of styrene and its derivatives, and in olefin-styrene copolymerization [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The titanium complex of the tetradentate [OSSO]-type diphenolate ligand with the 1,4-dithiabutanediyl-bridge yielded isotactic PS at very high activity.…”
Section: Introductionmentioning
confidence: 99%
“…The zirconium complex produced exclusively oligomers with even numbers of carbon atoms while its titanium analogue gave branched polymers [9,12]. Another zirconium complex as well as the hafnium one, having a ligand bearing trans-1,2-cyclooctanediylbis(thio) core, were highly active in 1-hexene polymerization providing highly isotactic poly(1-hexene) [15,16]. It was also shown that the regioselectivity during 1-hexene oligomerization switched when the titanium metal center was replaced with its heavier homolog (Zr, Hf) [10].…”
Section: Introductionmentioning
confidence: 99%